New mutation in Fabry disease: c.448delG, first phenotypic description - Calabrese, Esteban (2021)
Fabry disease (FD) (Anderson-Fabry disease, OMIM 301500) is a genetic disorder caused by a pathogenic variant in the GLA gene on chromosome Xq22 that produces a deficiency in the lysosomal enzyme alpha-galactosidase A. It is transmitted as an X-linked trait, although de novo mutations have been described. The objective of this report is to describe the clinical characteristics of a patient with FD who is a carrier of a mutation not previously studied, in order to provide information on the genotype-phenotype correlation in this pathology. 38-year-old patient who consulted Neurology for positional vertigo. He also reported acroparesthesia, anhidrosis, heat intolerance and episodes of abdominal pain, with postprandial discomfort from 10 years of age. Physical examination showed horizonto-rotatory nystagmus in both looks, the rest of the neurological evaluation did not present abnormalities. The presence of umbilical and thighs angiokeratomas was identified. Determination of Alpha-Galactosidase in blood was requested: 0.34 μmol/l/h (2.10–10.51 μmol/l/h). Genetic analysis detected a deletion of a guanine at position 448, in exon 3 of the GLA gene (c.448delG). This mutation was considered to be pathogenic, confirming the diagnosis of FD, although it is not described in the data bases. Genetic counseling and a family pedifree study were performed without finding relatives with this variant of the GLA gene or a family history of FD, which suggests a de novo mutation.